Representation of time intervals in a double bisection task: relative or absolute? - Maia, Susana Manuela Santos (2009)
We examined if the representation of time intervals in a temporal discrimination task is based not only on their absolute but also on their relative durations. Six pigeons learned two temporal discriminations. In the first, red and green choices were correct following 2-s and 8-s samples, respectively. In the second, vertical and horizontal bar choices were correct following 4-s and 16-s samples, respectively. In a previous study [Zentall, T.R., Weaver, J.E., Clement, T.S., 2004. Pigeons group time intervals according to their relative duration. Psychon. Bull. Rev. 11, 113-117.]. tests with 4-s samples and red/green comparisons revealed a bias for red, whereas tests with 8-s samples with vertical/horizontal comparisons revealed a bias for horizontal. These results were interpreted in terms of relative encoding of sample durations. We attempted to replicate this finding but instead of testing with only 4-s or 8-s samples, we tested with several other sample durations to obtain a psychometric function. Results were inconsistent with the relative encoding hypothesis.